Effect of combined use of organic and inorganic sources of nutrients on soil biological indicators and yield in aerobic rice (Oryza sativa) - SANGOTHARI, A; RADHAMANI, S; GNANACHITRA, M (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during the summer 2022 and navarai (December 2022–April 2023) seasons at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to evaluate the impact of different sources of nutrients on soil biological indicators and yield of rice (Oryza sativa L.) under aerobic conditions. Cultivation of aerobic rice with and without daincha (Sesbania aculeate) intercropping along with different sources of nutrients [M1, Rice alone and M2, Rice + Dhaincha intercropping and sub plot treatments were S1, Control; S2, Full dose of RDN (Recommended Dose of Nitrogen) from inorganic fertilizer; S3, Half dose of RDN from inorganic fertilizer + half dose of RDN from enriched farmyard manure (EFYM); S4, Half dose of RDN from inorganic fertilizer + half dose of RDN from EFYM + AM fungi + foliar nutrients (0.5% urea + 1% FeSO₄ + 0.5% ZnSO₄ at 25 and 45 DAS); S5, Half dose of RDN from inorganic fertilizer + quarter dose of RDN from EFYM + quarter dose of RDN from vermicompost (VC), top-dressed at 25 DAS and S6, Half dose of RDN from inorganic fertilizer + quarter dose of RDN from EFYM + quarter dose of RDN from VC + AM fungi + foliar nutrients (0.5% urea + 1% FeSO₄ + 0.5% ZnSO₄ at 25 and 45 DAS)] were tested in a split plot design (SPD) replicated thrice. In both the seasons, incorporation of daincha (M2) along with half dose of RDN from inorganic fertilizer + quarter dose of RDN from EFYM + quarter dose of RDN from VC + AM fungi + foliar nutrients of 0.5% urea + 1% FeSO₄ + 0.5% ZnSO₄ (S6) recorded the highest soil microbial biomass, enzymes activity and yield (3777 and 4599 kg/ha, respectively) of rice under aerobic condition. Therefore, combined use of organic and inorganic nutrient sources serves as a sustainable and effective strategy to improve soil health, enhance biological indicators and increase the yield of aerobic rice.